BREASTFEEDING AND POSTMENOPAUSAL OSTEOPOROSIS - Horia Lăzărescu; Daniela Miricescu; Ana Maria Alexandra Stănescu; Andrei Kozma; Constantin Ştefani; Florin Brezan; Maria Greabu; Alexandra Totan (Romanian Medical Journal, 2019)
The bone is a specialized connective tissue, consisting of type 1 collagen fibers and minerals represented as hydroxyapatite crystals. Osteoporosis is a common condition among menopausal women. Breastfeeding has beneficial effects on the health of both the baby and the mother. The purpose of this review is to analyze the results of specialized clinical studies on the effects of breastfeeding and the incidence of postmenopausal osteoporosis.